(untitled) (Journal of actual problems of jurisprudence, 2020)
Abstract. The right to vote is one of the most important rights of citizens of the Republic, allowing them to participate in the management of state affairs, in the formation of the highest echelon of power by the people. The article is devoted to the study of the protection of citizens’ electoral rights and their importance. The article deals with the electoral law as a form of participation of citizens in the management of state affairs, its constitutional and legal consolidation, the place and role of the institution of elections in the functioning of the state, the constitutional basis for the protection of electoral rights of citizens in the Republic of Kazakhstan. The article considered main causes of violations of electoral rights were identify and ways to protect them were identified. In States that affirm the true popular community, voting rights recognize the most accessible and often used constitutional possibility of citizen interference in state and local power, direct participation of citizens in the state and local issues. However, the constitutional and legal consolidation of the suffrage as a form of participation of the population in the management of state affairs does not provide a full basis for determining the democratic nature of the state. The elected rights of citizens in state-legal instruments are not only enshrined, but in real terms can be observed the formal, realistic nature of the democracy of any state, if they have found and implemented their action in real terms Life. Key words: democracy, the right to vote, source of state power, democratic state, protection of electoral rights.